Purificação de biodiesel de óleo de canola por adsorção em carvão ativado - Oliveira, Matheus Pereira de (2016)
This paper studied the purification process of biodiesel produced from crude and refined canola oil through alkaline route by using mineral activated carbon as adsorbent. The reaction occurred at 30ºC for crude canola oil and at 60ºC for refined canola oil. The molar ratio of 1:7.5 was used for both types of oil as well as a 1% solution of sodium hydroxide as catalyst. Out of this mixture, after 1 hour of reaction, the excess ethanol was removed by using a rotary evaporator and subsequently the reaction mixture was placed inside a separating funnel to remove the resulting glycerol. To remove the free glycerin, the biodiesel was purified by using activated carbon at three different temperatures: 25, 40 and 65ºC. For refined biodiesel, at 40 and 65ºC, the activated carbon adsorbed more free glycerin while for crude biodiesel the best results were obtained at 65ºC. There was a 96.77% removal for refined biodiesel at 40ºC while for crude biodiesel the removal was of 97.28%. The model that better fitted the kinetics data was the pseudo-first order while Freundlich model was the one that better fitted the equilibrium isotherm experimental data. The free glycerin index of the biodiesel purified by both conventional and adsorption methods was below the limit established by the ANP (Brazilian Agency of Petroleum, Natural Gas and Biofuels), which is 0.02%